Acanthosis nigricans as a clinical marker of insulin resistance among overweight adolescents - Videira-Silva, A (2019)
PURPOSE: Acanthosis nigricans (AN) is a hyperpigmented dermatosis associated with obesity and insulin resistance (IR). There is no consensus whether AN extension scoring offers added value to the clinical estimation of IR. In this study we aimed to assess and score AN using both a short and an extended version of the scale proposed by Burke et al. and analyze the relationships of both versions with hyperinsulinemia and IR. METHODS: We analyzed data from 139 overweight adolescents (body mass index ≥85th percentile) aged 12-18 with (n=67) or without (n=72) AN who were followed at a pediatric obesity clinic. RESULTS: Adolescents with AN had higher levels of insulin (d=0.56, P=0.003) and HOMA-IR (d=0.55, P=0.003) compared to those without. Neither the short nor the extended versions of AN scores explained either hyperinsulinemia (β=1.10, P=0.316; β=1.15, P=0.251) or IR (β=1.07, P=0.422; β=1.10, P=0.374). The presence of AN alone predicted hyperinsulinemia and the presence of IR in 7.3% (β=2.68, P=0.008) and 7.1% (β=2.59, P=0.009) of adolescents, respectively. CONCLUSION: Screening for AN at the neck and axilla is a noninvasive and cost-effective way to identify asymptomatic overweight adolescents with or at risk of developing IR.